Perbedaan Komitmen dan Kinerja antara Manajer Proyek Konstruksi Besar dan Manajer Proyek Konstruksi Kecil dengan Pendekatan Analisis Diskriminan - Sahadi, Sahadi; Agung Wibowo, M. (Department of Civil Engineering, Diponegoro University, 2014)
This study aims to analyze, first, the difference of commitment between big and small construction project managers, second, the difference of performance between big and small construction project managers. In particular, the commitment has eleven (11) discriminating indicator variables and the performance has nine (9) discriminating indicator variables. The results of study using the discriminant analysis approach indicate that from the eleven (11) indicator variables of commitment only two (2) indicator variables that discriminate big and small construction project managers, namely a. Y15= you are very concerned with the fate of this company, b. Y110= this company highly respects your values and goals, and from the 9 (nine) indicator variables of performance only one indicator variable that discriminates big and small construction project managers, namely Y26= the attitude towards work implementation